CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE - Hirawati, Heni; Giovanni, Axel; Sijabat, Yacobo (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The company's performance describes a company's financial condition that reflects work performance in a certain period. The company's performance is also determined by the ability to compete against other companies. The company's competitive ability can be improved through good corporate governance and utilising the company's intellectual capital. The change in management pattern from labour-based business to knowledge-based business has triggered the growing interest in intellectual capital disclosure. This study aims to provide empirical evidence regarding the role of intellectual capital and governance in explaining the variability of corporate financial performance. This study uses samples of 20 state-owned companies (BUMN) listed on the Indonesia Stock Exchange for 2015-2020. Analysis of research data with panel data regression using STATA. The results show that Corporate Governance and Intellectual Capital have no significant effect on the BUMN financial performance. In the control variables consisting of Leverage, Firm Size, and Company Age, only leverage influences the company's financial performance